(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Issues of onomastics have been relevant for every era. Uzbek nomenclature has a specific stage of development. Especially, the study of the development of atroponyms at the beginning of the 20th century provides important scientific conclusions for Uzbek onomastics. The goal is to study the development of anthroponyms in the beginning of the 20th century, their structural-semantic features, and to analyze them from a historical-etymological and linguistic-cognitive point of view. In the implementation of this goal, the tasks of describing anthroponyms of the beginning of the 20th century, analyzing anthroponyms in artistic works, carrying out statistical, historical-etymological and linguo-cognitive analysis, and structural study are defined.